ANALYSIS OF SOLAR ENERGY PARAMETERS IN BIDA, NIGERIA - G.N., Okonkwo; A.O.C., Nwokoye (European Scientific Journal, ESJ, 2014)
The monthly daily average solar energy parameters measured in Bida (9.1°N, 6.02°E) for a period of thirteen years (2000 – 2012) were obtained from the Nigerian Meteorological Agency Bida, Niger State. These data which include Gunn-Bellani solar radiation, sunshine hour duration, relative humidity, rainfall, wind speed, maximum and minimum temperatures were analysed using both single-variable and multi-variable regression techniques of the Angstrom type to generate several regression equations (models) that were used to estimate the total solar radiation reaching a horizontal surface in Bida. The statistical error methods of the mean bias error (MBE), root mean square error (RMSE), mean percentage error (MPE) and T-test were used to test the performances of these models. The correlation coefficient (R) and coefficient of correlation (R2) were also determined for each model. Based on the highest values of correlation coefficient (R) and coefficient of determination (R2) and least RMSE value, the equation (model 9) that outperformed the rest is: . This model is recommended for designers and engineers of solar energy and other renewable energy devices in this area.